Domain zipping and unzipping modulates TRPM4's properties in human cardiac conduction disease. Issue 9 (17th July 2020) - Xian, Wenying; Wang, Hongmei; Moretti, Alessandra; Laugwitz, Karl‐Ludwig; Flockerzi, Veit; Lipp, Peter
Abstract: The transient receptor potential melastatin 4 (TRPM4) is a Ca 2+ ‐activated nonselective cation channel linked to human cardiac diseases. The human mutation K914R within TRPM4's S4‐S5 linker was identified in patients with atrioventricular block. During UV‐flash‐mediated Ca 2+ transients, TRPM4 K914R generated a threefold augmented membrane current concomitant with 2 to 3‐fold slowed down activation and deactivation kinetics resulting in excessive membrane currents during human cardiac action potentials. Mutagenesis of K914 paired with molecular modeling suggested the importance of the nanoscopic interface between the S4‐S5 linker, the MHR4‐, and TRP‐domain as a major determinant for TRPM4's behavior. Rational mutagenesis of an interacting amino acid (R1062Q) in the TRP domain was able to offset K914R`s gain‐of‐function by zipping and unzipping of this nanoscopic interface. In conclusion, repulsion and attraction between the amino acids at positions 914 and 1062 alters the flexibility of the nanoscopic interface suggesting a zipping and unzipping mechanism that modulates TRPM4's functions. Pharmacological modulation of this intramolecular mechanism might represent a novel therapeutic strategy for the management of TRPM4‐mediated cardiac diseases.